Editorial - ILM: To Peel or Not to Peel - Iqbal, Mustafa (Pakistan Journal of Ophthalmology, 2015)
I was first introduced to Internal Limiting Membrane (ILM) peeling in 1996 by Prof. Eckardt on his visit to Moorfields Eye Hospital. His elegant videos of ILM peeling were carried out without the help of any dye and were inspiring. Prof Eckardt subsequently published his work in 19971 . Morris et al had performed ILM peeling in 1990 for Haemorrhagic retinal cysts and published their 7 year followup in 19972 . This report also demonstrated the long term safety of ILM peeling. ILM is only 6 micron thick and is the structural boundary between the retina and the vitreous. It is adherent to the collagenous cortex of the vitreous on its one side, and to the Muller (glial) cell end feet on the Retinal side3 .